Diverse criteria’s-disparate prevalence rates: prevalence of metabolic syndrome by modified NCEP-ATP III and IDF criteria - B. Shetty, Surekha; Lalitha, R; Kumar R, Anil (International Journal of Medical Research and Review, 2016)
Background: Metabolic syndrome is a cluster of metabolic risk factors including central obesity, glucose intolerance, atherogenic dyslipidemia and hypertension. Studies have shown a prevalence of 10 - 84% in general population and 57- 92% in type 2 diabetic patients. Aims and Objectives: Our study aims to establish the prevalence of metabolic syndrome in diabetic patients at Karnataka Institute of Diabetology, Bangalore. It aims to compare the prevalence using modified NCEP-ATP III and IDF criteria, and also in women and men. Methodology: A cross-sectional study was conducted in 402 (38.6% women, 61.4% men) type 2 diabetic subjects. Fasting blood glucose, lipid profile, waist circumference and blood pressure were recorded. Modified NCEP-ATP III and IDF criteria were used to calculate the prevalence of metabolic syndrome. Results: The prevalence of metabolic syndrome was 75.1% by modified NCEP-ATP III and 68% by IDF criteria. The prevalence was 94% and 92% in women and 62% and 54% in men, by modified NCEP-ATP III and IDF criteria respectively. Hypertension was the commonest component in men, and high waist circumference was the commonest component in women. Nearly 50% had 4 components of metabolic syndrome, ≈30% had 3 components and ≈25% had all the 5 components. Conclusions: The prevalence of metabolic syndrome is very high among diabetic patients. It is higher using modified NCEP-ATP III compared to IDF criteria, especially in men. The prevalence is higher in women, due to central obesity. Hence, all type 2 diabetic patients must be evaluated for metabolic syndrome.